EMBEDDING LOCAL WISDOM IN CURRICULUM: A PATHWAY TO SUSTAINABLE AWARENESS IN HIGHER EDUCATION - Carolina, Hifni Septina; Rochintaniawati, Diana; Riandi (International Conference on Education, Science, Technology and Health (ICONESTH), 2025)
In the fight against environmental degradation, local wisdom and the SDGs are intertwined. Students learn sustainability and local culture through local wisdom in the university curriculum. This study aims to describe the implementation of local wisdom and environmental ethics lectures to foster students' sustainability awareness. This study uses data collection techniques based on document review, questionnaires and interviews. The examined documents comprise the curriculum, textbooks, and additional instructional materials utilised in education. Surveys and interviews were administered to lecturers and students. The findings indicated that (1) the execution of lectures on local wisdom and environmental ethics is proceeding effectively, (2) the incorporation of local wisdom and environmental ethics into the curriculum requires enhancement to facilitate students' comprehension of the material in a tangible and factual context, (3) students exhibit commendable knowledge and awareness of sustainability. This study suggests that learning that includes sustainable principles based on local wisdom promotes meaningful experience and sustainable awareness growth. Keywords: local wisdom, curriculum, sustainable awareness